6a-(a-1)=4

Simple and best practice solution for 6a-(a-1)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a-(a-1)=4 equation:


Simplifying
6a + -1(a + -1) = 4

Reorder the terms:
6a + -1(-1 + a) = 4
6a + (-1 * -1 + a * -1) = 4
6a + (1 + -1a) = 4

Reorder the terms:
1 + 6a + -1a = 4

Combine like terms: 6a + -1a = 5a
1 + 5a = 4

Solving
1 + 5a = 4

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 5a = 4 + -1

Combine like terms: 1 + -1 = 0
0 + 5a = 4 + -1
5a = 4 + -1

Combine like terms: 4 + -1 = 3
5a = 3

Divide each side by '5'.
a = 0.6

Simplifying
a = 0.6

See similar equations:

| 6x-91=3x-10 | | 214-2x=34x+18 | | 9-6z=27 | | 4g+3(-7+2g)=1-g | | 14-7x=174-42x | | 2g+4(-6+2g)=1-g | | 36x=x*(r*r) | | 6x-91=3x-2 | | t^2-2t-36=0 | | -6g-4=-3g+2 | | 3x-4=4x-2 | | 3x-4=4x-ray | | -8=-2a+6 | | x^3-7x= | | 3x+29=11x-43 | | -6m+69-9(m-1)=4m-(2m-2)-7m+6 | | 10y^2-19y+6=0 | | 6p-8=8-30p | | 93=9*(e^2x) | | 2x+8=64-4x | | -3r+7=5r-3 | | 5.2y+7.2=30.6-1.3y | | 4b-21=28 | | y=4-3*2 | | 104-7x=29x+24 | | 0.47x=-3.23x+62.9 | | 93=9e^2x | | 7=9x-1 | | c+0.1c+0.01c-0.001c=c+0.545 | | 36-6x=18+3x | | n^2+n-400=0 | | 3(r-3)-r=-4(2r+5)-8 |

Equations solver categories